# Find the maximum value of the expression $P = {{x} ^ {2}} - \frac {3} {4x} - \frac {x} {y}$ [closed]

For positive real numbers x, y satisfy the condition $x + y \le$1. Find the maximum value of the expression $$P = {{x} ^ {2}} - \frac {3} {4x} - \frac {x} {y}$$ (Please help not to use derivative because this way I solved. Only use basic inequalities)

## closed as off-topic by Martin R, Arnaud D., Namaste, GNUSupporter 8964民主女神 地下教會, polfosolApr 9 '18 at 13:01

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Martin R, Arnaud D., Namaste, GNUSupporter 8964民主女神 地下教會, polfosol
If this question can be reworded to fit the rules in the help center, please edit the question.

$$P(x,y)-P\left(\frac{1}{2},\frac{1}{2}\right)=-\frac{(1-x-y)x}{y(1-x)}-\frac{(2x-1)^2\left(x^2+3\right)}{4x(1-x)}\leq 0$$

Clearly, for $y_0<y_1$ we get

$$x^2- \frac {3} {4x} - \frac {x} {y_0}<x^2- \frac {3} {4x} - \frac {x} {y_1}$$

for any $x$, so this means the maximum will have the largest possible $y$. Since $x+y\leq 1$, this must be $y=1-x$. This means we are searching for the maximum of

$$P=x^2-\frac{3}{4x}-\frac{x}{1-x}$$

where $0<x<1$. We will first rewrite it:

$$P=x^2-\frac{4x^2-3x+3}{4x(1-x)}$$

Now since $4x(1-x)$ is symmetric over $\tfrac12$, we will substitute $z=x-\tfrac12$ and we get

$$P=(\tfrac12+z)^2-\frac{4(\tfrac12+z)^2-3(\tfrac12+z)+3}{4(\tfrac12+z)(\tfrac12-z)}$$

which simplifies to

$$P=(\tfrac12+z)^2-\frac{4z^2+z+\tfrac52}{1-4z^2}$$

and now we'll write the whole thing as one fraction:

$$P=-\frac{4z^4+4z^3+4z^2+\tfrac{9}4}{1-4z^2}$$

and from this, we can see it is useful to write it as

$$P=-4z^2\frac{z^2+z+1}{1-4z^2}-\frac{\tfrac94}{1-4z^2}$$

Now simply note that $z^2+z+1>0$ on $|z|<\tfrac12$, so that $\frac{z^2+z+1}{1-4z^2}$ is positive; together with $-4z^2\leq 0$, this means

$$-4z^2\frac{z^2+z+1}{1-4z^2}\leq 0$$

where equality is being reached at $z=0$. Luckily, we also see the maximum of the other term $\frac{9/4}{1-4z^2}$ has a maximum at $z=0$ too (since $1-4z^2\leq 1$ so that $-\tfrac{9/4}{1-4z^2}\leq -\tfrac94$). This means the maximum of $P$ is being found at $z=0$ or $x=\tfrac12$, and $P=-\tfrac94$.

• Unless I am mistaken, $x^2-\frac{3}{4x}-\frac{x}{1-x}$ approaches $-\infty$ for $x \to 1$, and the function has a maximum somewhere in the interior of the interval. – There seems to be an error at $P=x^2+\frac{4x^2+3x-3}{4x(1-x)}$. – Martin R Apr 9 '18 at 9:48
• Yup! Lost a minus sign on the way. Thanks for pointing that out! – vrugtehagel Apr 9 '18 at 10:46